Effect of Board Characteristics on Financial Performance of Listed Healthcare Firms in Nigeria - Samuel Enejoh Abu; Obaya Moses Bamidele (Annals of Management and Organization Research, 2022)
Purpose: This study was conducted to investigate the relationship between board characteristics and the financial performance of listed healthcare firms in Nigeria. Research methodology: The study, which covered a seven-year period from 2015-2021, made use of secondary data sourced from published annual reports and accounts of five purposively selected companies on the Nigerian Stock Exchange. Data analysis was done by means of descriptive statistics, a correlation matrix, and some diagnostic tests using STATA 13. Results: The findings show that board characteristics consisting of board size, board independence, board gender diversity, and board meetings have a negative, non-significant relationship with performance. This study concludes that board size should be increased, the number of non-executive members of the board should be increased with members having vast knowledge and competency in governance, the number of women on the board should be increased, and frequent and necessary board meetings should be encouraged and possibly regulated in order not to create room for waste of resources and time. Limitations: The study’s main limitations are that it did not use other financial-based measurements for financial performance, used incomplete data, and used a small sample size. Contribution: The results of the study, based on the findings, will assist firms in the recommendation of the board size number and how its effectiveness should be increased and sustained. The study also contributes to other extant literature, as not many studies have been conducted in this area of the healthcare firms listed on the Nigerian Stock Exchange.